Advanced Cancer Patients’ Changes in Accurate Prognostic Understanding and Their Psychological Well-Being - George, Login S. (J Pain Symptom Manage, 2019)
CONTEXT: Clinicians often worry that patients’ recognition of the terminal nature of their illness may impair psychological well-being. OBJECTIVES: To determine if such recognition was associated with decrements to psychological well-being that persisted over time. METHODS: Eighty-seven advanced cancer patients, with an oncologist-expected life-expectancy of less than 6 months, were assessed before and after an oncology visit to discuss cancer restaging scan results, and again at follow-up (median time between assessments, approximately 6 weeks). Prognostic understanding (PU) was assessed at pre- and post-visit, and a change score was computed. Psychological well-being was assessed at pre, post, and follow-up, and two change scores were computed (post minus pre; follow-up minus post). RESULTS: Changes toward more accurate PU was associated with a corresponding initial decline in psychological well-being (r = −0.33, p < .01), but thereafter was associated with subsequent improvements (r = .40, p < .001). This pattern remained controlling for potential confounds. Patients showed different patterns of psychological well-being change (F = 3.07, p = .05; F = 6.54, p < .01): among patients with improved PU accuracy, well-being initially decreased, but subsequently recovered; by contrast, among patients with stable PU accuracy, well-being remained relatively unchanged, and among patients with decrements in PU accuracy, well-being initially improved but subsequently declined. CONCLUSION: Improved PU may be associated with initial decrements in psychological well-being, followed by patients rebounding to baseline levels. Concerns about lasting psychological harm may not need to be a deterrent to having prognostic discussions with patients.